Non-albumin proteinuria marks tubular involvement and is associated with arterial stiffness in subjects affected by severe obesity - Moriconi, Diego; Nannipieri, Monica; Armenia, Silvia; Taddei, Stefano; Solini, Anna; Bruno, Rosa Maria (Obesity research & clinical practice, 2023)
Obesity is a well-established risk factor for kidney disease, and tubular damage can play a pivotal role in the development of obesity-related kidney damage. This study aimed to investigate the pathophysiological pathways involved in the development of non-albumin proteinuria (NAP), a marker of tubular involvement, in a cohort of subjects with severe obesity and preserved kidney function. A total of 106 subjects with BMI ≥ 35 kg/m2 in waiting list for bariatric surgery underwent blood chemistry analysis including metabolic and lipid profile, vascular tests for cardiovascular risk stratification and a comprehensive assessment of kidney function, including renal resistive index (RRI) and NAP measurement. Nineteen patients with ACR ≥ 30 mg/g regardless of NAP values (ALB+), nineteen with NAP≥ 150 mg/g and albuminuria < 30 mg/g (iNAP) and sixty-eight without proteinuria (No-P) were found. Both ALB+ and iNAP groups exhibited a higher prevalence of hypertension and anti-hypertensive treatment compared to No-P, while the prevalence of diabetes was similar between groups. Concerning lipid profile, no differences in total, HDL and LDL cholesterol were found, while ALB+ patients had higher serum triglyceride levels than the other two groups. RRI and carotid-femoral pulse wave velocity (cf-PWV) was significantly higher in ALB+ and iNAP groups compared to No-P. Remarkably, cf-PWV remained still significant after adjustment for age, sex and MBP (p = 0.0004). In overall population, a multiple regression analysis showed that cf-PWV was an independent determinant of NAP in a model including age, sex, glycated hemoglobin, systolic and mean blood pressure (R2 =0.17, p = 0.031). iNAP subjects showed increased arterial stiffness comparable to that observed in ALB+ group, suggesting that they may represent a subgroup at higher cardiovascular risk, often unrecognized in clinical practice.